Preliminary comments on malacofauna in some small sambaquis of the South Coast of Santa Catarina - Heitzmann-Fontenelle, José; Tognoli, Anderson Rogério de Oliveira; Demathe, Alexandro (Revista do Museu de Arqueologia e Etnologia, 2021)
Malacofauna present in six small sambaquis located in Jaguaruna-SC aged between 3080 and 580 yBP (Eliza, Encruzo, Campo Bom I, Campo Bom II, Campo Bom III and Arroio da Cruz I) was performed. We identified 22 species of mollusks, 10 gastropods and 12 bivalves. All species were marine or estuarine with the exception of two terrestrial snail species Megalobulimus. Two distinct patterns were found regarding the constitution of the malacological matrix of the sites. In older sambaquis (Eliza and Encruzo) there was greater diversity of species, majority coming from a lagoon and estuarine paleoenvironment (Anomalocardia brasiliana, Phacoides pectinatus and Erodona mactroides) including mangrove (Cassostrea brasiliana), with great variation in intraspecific size and occurrence of individuals with closed valves. In the most recently dated sambaquis (Campo Bom I, II and III, and Arroio da Cruz I) there was the majority presence of open sea coast species (Mesodesma mactroides and Donax hanleyanus) with greater intraspecific uniformity in size, however the malacological matrix Campo Bom II was differentiated by the additional occurrence of large individuals of the bivalve Tivela zonaria and the gastropod Pachycymbiola brasiliana, inferring a differentiated construction. This study reinforced the importance of evaluating the malacological matrix in sambaquis as indicative of the paleoenvironment and the cultural options of its builders, as well as the diversity of species could suggest a distinct use or function of the site.